PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH DALAM PENINGKATAN PEMBELAJARAN BAHASA INGGRIS SISWA KELAS IV SDN 2 JOGOPATENTAHUN AJARAN 2012/2013 - Muliyana, Putri (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: The Application of Make a Match Learning in Improving Student Learning Integer Class IV SDN 2 JogopatenAcademic Year 2012/2013. This study aims to: (1) describe the learning process, (2) improving english learning, and (3) the constraints and possible solutions. This research was conducted in two cycles, each cycle includes the planning, implementation, observation, and reflection. The subjects were students of class IV SDN 2 Jogopatentotaling 21 students. Source of data derived from students, teachers, and documents. Data collection techniques were observation, testing, and documentation. Analysis technique of data used includes reduction of data, data presentation, and conclusing or verification. The percentage of student mastery before action was 70%, after the implemented action first cycle increased to 90%, and the second cycle increased to 100%. The results showed that the application of Make a Match learning can improve the learning integers fourth grade primary school students. Keywords: learning, STAD, media charge cards, integers Abstrak: Penerapan Model Pembelajaran Make a Match dalam Peningkatan Pembelajaran Bahasa Inggris Siswa Kelas IV SDN 2 JogopatenTahun Ajaran 2012/2013. Penelitian ini bertujuan: (1) mendeskripsikan langkah pembelajaran, (2) peningkatan pembelajaran matematika, dan (3) kendala dan solusinya. Penelitian ini dilaksanakan dalam dua siklus, masing-masing siklus mencakup tahap perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian ini adalah siswa kelas IV SDN 2 Jogopaten yang berjumlah 21 siswa. Sumber data berasal dari siswa, guru, dan dokumen. Teknik pengumpulan data adalah dengan observasi, tes, dan dokumentasi. Teknik analisis data terdiri dari reduksi data, penyajian data, dan penarikan kesimpulan atau verifikasi.Persentase ketuntasan siswa sebelum tindakan adalah 70%, setelah dilaksanakan tindakan siklus I meningkat menjadi 90%, siklus II meningkat menjadi 100. Hasilnya menunjukkan bahwa penerapan Model Pembelajaran Make a Match dapat meningkatkan pembelajaran Bahasa Inggris siswa kelas IV sekolah dasar. Kata kunci: pembelajaran, Make a Match, Bahasa Inggris